2011
DOI: 10.3354/meps09117
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen uptake by the shoots of smooth cordgrass Spartina alterniflora

Abstract: The smooth cordgrass Spartina alterniflora is the foundation species in intertidal salt marshes of the North American Atlantic coast. Depending on its elevation within the marsh, S. alterniflora may be submerged for several hours per day. Previous ecosystem-level studies have demonstrated that S. alterniflora marshes are a net sink for nitrogen (N), and that removal of N from flooding tidal water can provide enough N to support the aboveground biomass. However, studies have not specifically investigated whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…We suggest that there is potential for DON uptake by S. alterniflora in high-latitude salt marshes to account for more than the 24% of plant N demand previously reported for mid-latitude salt marshes (Mozdzer et al 2010(Mozdzer et al , 2011. We suggest that there is potential for DON uptake by S. alterniflora in high-latitude salt marshes to account for more than the 24% of plant N demand previously reported for mid-latitude salt marshes (Mozdzer et al 2010(Mozdzer et al , 2011.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…We suggest that there is potential for DON uptake by S. alterniflora in high-latitude salt marshes to account for more than the 24% of plant N demand previously reported for mid-latitude salt marshes (Mozdzer et al 2010(Mozdzer et al , 2011. We suggest that there is potential for DON uptake by S. alterniflora in high-latitude salt marshes to account for more than the 24% of plant N demand previously reported for mid-latitude salt marshes (Mozdzer et al 2010(Mozdzer et al , 2011.…”
Section: Discussionmentioning
confidence: 55%
“…We previously demonstrated that S. alterniflora can use DON directly via roots (Mozdzer et al 2010) as well as through foliar uptake (Mozdzer et al 2011), and that DON can provide up to 24% of plant N demand (Mozdzer et al 2010). Direct uptake of DON in salt marsh ecosystems may help explain the high productivity of oligotrophic marshes.…”
Section: Introductionmentioning
confidence: 99%
“…Based on recent data (2015), nutrient enrichment elevated porewater nitrate threefold in marsh sediments; however, porewater nitrate was still an order of magnitude lower than porewater ammonium, which did not vary significantly between treatments (T. Mozdzer, unpublished data). Second, foliar uptake rates of ammonium are six times higher than nitrate in S. alterniflora even given an order of magnitude difference in N-availability for nitrate in the water column (Mozdzer et al 2011). Third, as an anion, nitrate-N moves freely through our system and is likely exported before it can be used.…”
Section: Discussionmentioning
confidence: 92%
“…Second, foliar uptake rates of ammonium are six times higher than nitrate in S. alterniflora even given an order of magnitude difference in N‐availability for nitrate in the water column (Mozdzer et al. ). Third, as an anion, nitrate‐N moves freely through our system and is likely exported before it can be used.…”
Section: Discussionmentioning
confidence: 99%
“…SIC may account for more than 60 % of soil total carbon in wetlands of the Yangtze River estuary (Cheng et al 2006). Although S. alterniflora could reduce soil pH through secreting low molecular weight organic acids by roots (Hines et al 1994) and preferential uptake of NH þ 4 -N (Mozdzer et al 2011), mean pH value of the water near the Yangtze River estuary was *8.2 (Patra et al 2007). Thus, periodic tidal inundation can maintain the alkaline environment (pH [ 8.0) of soils, ensuring the stability of the SIC pool in the estuary.…”
Section: Tidal Effects On Soil Propertiesmentioning
confidence: 97%